Consumer protection facing globalisation: a comparative study between United Kingdom and Malaysia - Syed Sagoff Alsagoff (Fakulti Undang - Undang, 2006)

(untitled)
Consumer protection law has always been relied on as a mechanism to safeguard consumer interest and generate economic activities. The need for a more reliable mechanism is inevitable especially more so in the present era of globalization and flourishing E-Commerce activities. This article discusses the current trend of consumer protection laws, which has been embraced in the United Kingdom and the European Union. In the same tenor, the writer will address the current flaws and inadequacies of consumer protection laws in Malaysia in the face of globalization. The writer also concurrently proposes reforms aimed at injecting the concept of consumer welfarism